PENGARUH PRENATAL YOGA TERHADAP KECEMASAN MENGHADAPI PERSALINAN PADA PRIMIGRAVIDA - Alhidayati Alhidayati; Yusniarita Yusniarita; Derison Marsinova Bakara (Politeknik Kesehatan Kementerian Kesehatan Banten, 2022)
One indicator to measure the degree of health is maternal mortality. According to the World Health Organization (WHO) (2019), around 830 women die from complications during pregnancy and childbirth, where 94% of maternal deaths occur in developing countries including Indonesia. This study aims to determine the relationship of prenatal yoga on anxiety facing childbirth in primigravida Trimester III mothers.This study used a quasi-experimental design with a pre-test-post-test design with a control group. The population is Primigravida Trimester III pregnant women in the working area of ​​the Pasar Kepahiang Health Center as many as 120 people. A sample of 34 people consisted of 17 experimental groups and 17 control groups. Sampling in case groups by purposive sampling. Data were analyzed by Paired Sample t-test. The results showed the average anxiety in the experimental group before the intervention (pre-test) was 59.65 and after the intervention (post-test) was 43.76 while the average anxiety in the control group before the intervention (pre-test) was 57.59 and after the intervention (post-test) namely 52.53. There were differences in anxiety in the control group (p value = 0.004) and the experimental group (p value = 0,000) before and after the intervention. It is expected that midwifery health services can do prenatal yoga as an alternative in conducting midwifery care to reduce the level of anxiety of pregnant women